Customers as predictors of rent returns to innovation in small firms: an exploratory study. (3rd May 2005) - Mazzarol, Tim; Reboud, Sophie
Small to medium enterprises (SME) are frequently associated with high levels of innovation. However, it is difficult for such firms to fully assess the merits of a particular innovation. This study examined the risk-return profile of future investment in innovation by SME with respect to anticipated "rent" or financial returns. A survey of highly innovative SME was undertaken that examined management perceptions of the key strategic influences on rent returns. Regression analysis suggests that the firms' assessment of the rent returns from their innovation may be influenced by the value it is likely to deliver to the customer, the customer's expected use of the innovation to generate new sales and the ease of integrating the new innovation into existing technologies. The findings have implications for how entrepreneurs from early stage ventures are assisted.